The German experience of urban regeneration, taking the Blasewitz-Striesen Nord-Ost district (Dresden) as an example, and the possibility of its application in historical cities in Russia - Malko, Anastasia (International Planning History Society Proceedings, 2022)
The article illustrates the practical application of legislative and planning tools for the preservation and development of the historical and architectural urban environment in the city of Dresden, taking the districts of Blasewitz and Striesen as examples. It examines the principles of rapid response and countermeasures to the destruction of the historical, architectural and urban environment, as well as decision-making procedures and implementation mechanisms. Furthermore, it describes the distinctive features of the system of preservation of urban heritage in Germany which guarantee the effectiveness of preservation, and which can be considered as principles for applying the German experience to historical cities in Russia.